Fuzzy multicriteria decision-making for assessing multinational enterprises’ outbound investment destinations on the basis of tax factors - Chu, Chun-Chieh; Hsu, Ping-Yu; Lu, Shih-Tong (Technological and Economic Development of Economy, 2025)
Taxes are a crucial consideration in a multinational enterprise’s (MNE)’s choice of overseas market to invest in. Taxes are affected by a variety of factors, and these factors are prioritized vis-à-vis each other in such investment decision-making. The present study thus developed a framework for evaluating the relative importance of tax factors affecting the outbound investment decisions of MNEs, using insights from the literature and expert interviews to establish evaluation criteria. To address the complexities of multicriteria decision-making, this study employed fuzzy linguistic preference relations. The study subsequently applied the fuzzy Vlse Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR) approach to rank the alternatives proposed by the expert decision-making group. Finally, this study applied this methodology to a case study of candidate overseas markets (Vietnam, Malaysia, and Indonesia) for Taiwanese firms to invest in, providing a practical demonstration of the model. In conclusion, the present study’s comparative analysis of the application of fuzzy VIKOR to foreign direct investment by Taiwanese MNEs offers a systematic approach for both academic and industry practitioners involved in strategic host country selection for multinational investments.First published online 14 July 2025